ANALISIS DAN EVALUASI MANAJEMEN RISIKO PADA USAHA LAUNDRY RUMAHAN MENGGUNAKAN METODE LIKELIHOOD DAN CONSEQUENCE RISK MATRIKS - Faradillah, Jihan Muhrifa; Rachmadhani, Mirga Maulana; Kadang, Dirgantari Ria; Mahmud, Fadila; Amri, Irman (Universitas Muhammadiyah Sorong, 2024)
Home laundry business has become a popular entrepreneurial option in Indonesia due to its ease of start-up and the increasing need for laundry services. However, this business also faces various risks that need to be managed properly to ensure its sustainability and success. This study aims to evaluate risk management in home-based laundry businesses in Sorong City using the Likelihood and Consequence Risk Matrix method. This method combines the criteria of risk likelihood and consequence to quantify and prioritize risks. Data was obtained through surveys and direct interviews with respondents and literature studies from various sources. Data analysis was conducted using Descriptive Analysis. The identification results show that there are nine main risks divided into operational, financial, strategic, and fraud categories. These risks were then analyzed and scored based on their likelihood and impact. The findings show that exposure to hazardous chemicals (R1) and timeliness of pick-up and delivery (R4) are the highest risks and require immediate mitigation actions. Suggested mitigations include the use of safe chemicals, employee training, provision of personal protective equipment, and improved transportation management. By implementing these mitigation strategies, it is expected that home-based laundry businesses can reduce the negative impact of the identified risks and improve operational efficiency and business sustainability. This research provides significant insights for home laundry business owners and researchers in the field of small and medium enterprise risk management.